Model to improve the efficiency in the extrusion area in a manufacturing sme of the industrial plastic sector based on smed, autonomous maintenance and 5s - Arroyo-Huayta, Carlos (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.